Multicoletor de óleo isolante para transformador de potência - FRANÇA, Lucas Alves (2019)
The project in question is initially applied to the 500 kV voltage transformer system that is connected to the hydraulic generating units of the TUCURUÍ Hydroelectric Power Plant. It is known that the process of collecting mineral insulating oil is essential in the predictive maintenance of power transformers. As the collection point is fixed in the transformer itself, the environment that the collecting specialist performs the procedure is considered dangerous. Due to the occurrence of the accident in one of the transformers, it was not advisable to collect oil with the energized transformer, contrary to Norm NBR-7070. The multicoletor was designed to meet the four collection points, one in the transformer reservoir and three in the high nozzle points, without changing the quality of the samples. The implemented improvement allows the collection of oil with the energized transformer at a safe distance without impacting on the productive process of power generation of UHE-TUCURUÍ.